Non-vanishing of L-functions associated to cusp forms of half-integral weight in the plus space - Kohnen, Winfried; Raji, Wissam (Research in number theory, 2017)
In this paper, we show a non-vanishing result for L-functions associated to cuspidal Hecke eigenforms of half integral weight in plus space.